Effect of Sodium Fluoride on Seed Germination and Seedling Growth of Triticum aestivum var. Raj. 4083 - Bhardwaj, Devika Bhargava* and Nagendra (Journal of Phytology, 2010)
<span style="font-size: 10pt; line-height: 110%; font-family: ";Book Antiqua";,";serif";; mso-fareast-font-family: SimSun; mso-fareast-language: ZH-CN; mso-ansi-language: EN-US; mso-bidi-font-family: 'Times New Roman'; mso-bidi-language: AR-SA;">Fluoride contamination in water, soil and plants has been a continuing problem in the world. The effects of 4, 8, 12, 16 and 20 mg/L sodium fluoride (NaF) were studied on Triticum aestivum var. Raj. 4083 seeds and seedling growth. After 7 days of treatment with control, 100% germination occurred, but at 20 mg NaF/L, germination was reduced to 88%. Physiological parameters, viz., root length, shoot length and dry weight decreased with increasing NaF concentration. At 20mg NaF/L, the average root length, shoot length and dry weight were reduced by 36.6%, 24% and 20.54% respectively. At 20 mg NaF/L, Vigor index was reduced by 37.20% compared to control. The chlorophyll content of the leaves was also reduced monotonically. At 20mg NaF/L, it was 0.074 mg/g which was 27.45% lesser compared to control. Ascorbic acid content initially decreased and then increased with increasing concentration of NaF (20mg/L).So our study concludes that sodium fluoride has significant impact on seed germination and seedling growth of wheat.